Mitochondria are required for pro‐ageing features of the senescent phenotype. (4th February 2016) - Correia‐Melo, Clara; Marques, Francisco DM; Anderson, Rhys; Hewitt, Graeme; Hewitt, Rachael; Cole, John; Carroll, Bernadette M; Miwa, Satomi; Birch, Jodie; Merz, Alina; Rushton, Michael D; Charles, Michelle; et al.
Abstract: Cell senescence is an important tumour suppressor mechanism and driver of ageing. Both functions are dependent on the development of the senescent phenotype, which involves an overproduction of pro‐inflammatory and pro‐oxidant signals. However, the exact mechanisms regulating these phenotypes remain poorly understood. Here, we show the critical role of mitochondria in cellular senescence. In multiple models of senescence, absence of mitochondria reduced a spectrum of senescence effectors and phenotypes while preserving ATP production via enhanced glycolysis. Global transcriptomic analysis by RNA sequencing revealed that a vast number of senescent‐associated changes are dependent on mitochondria, particularly the pro‐inflammatory phenotype. Mechanistically, we show that the ATM, Akt and mTORC1 phosphorylation cascade integrates signals from the DNA damage response (DDR) towards PGC‐1β‐dependent mitochondrial biogenesis, contributing to a ROS‐mediated activation of the DDR and cell cycle arrest. Finally, we demonstrate that the reduction in mitochondrial content in vivo, by either mTORC1 inhibition or PGC‐1β deletion, prevents senescence in the ageing mouse liver. Our results suggest that mitochondria are a candidate target for interventions to reduce the deleterious impact of senescence in ageing tissues. Synopsis: Cellular senescence serves as an important anticancer growth arrest mechanism, but also contributes to ageing. This study shows that mitochondria are necessary for the pro‐inflammatory phenotype during senescence and that senescence can be induced by mitochondrial biogenesis. Mitochondria are required for the development of the pro‐oxidant and pro‐inflammatory features of senescence. ATM, Akt, mTOR and PGC‐1β‐mediated mitochondrial biogenesis are involved in a novel senescence signalling pathway. Mitochondrial biogenesis stabilizes senescence via a positive feedback loop involving ROS and the DDR. Abstract : Cellular senescence serves as an important anticancer growth arrest mechanism, but also contributes to ageing. This study shows that mitochondria are necessary for the pro‐inflammatory phenotype during senescence and that senescence can be induced by mitochondrial biogenesis.